Successful use of extracorporeal membrane oxygenation for pulmonary embolism, prolonged cardiac arrest, post-partum: a cannulation dilemma. (March 2015) - Fernandes, P; Allen, P; Valdis, M; Guo, L
A 30-year-old female gravida 1 (37 weeks + 5 days gestation) underwent a crash Cesarean section for evidence of fetal distress, with the presumed diagnosis of placental abruption. Immediately post-op, the patient had a complete cardiovascular collapse with pulseless electrical activity, requiring cardiopulmonary resuscitation (CPR). Two doses of thrombolytics (Tenecteplase) were administered during the resuscitation, with a presumed diagnosis of a pulmonary embolism. After approximately 45 minutes into the resuscitation, the cardiac surgery team was called to initiate extracorporeal membrane oxygenation (ECMO). Case Study: Veno-arterial (V-A) ECMO was emergently attempted, with difficulty, through a left femoral cut-down approach and was successfully initiated 84 minutes into the resuscitation. Once the patient's blood pressure and oxygen saturations were stabilized, the cannulae were switched to the right groin, using a Dacron graft in an end-to-side fashion. The left groin vessels were small and spasmodic due to CPR, hypotension, hypovolemia and massive inotropes. The switch helped to facilitate repair of the left femoral vessels in order to restore perfusion to the left leg. Computer tomography (CT) demonstrated multiple pulmonary emboli at the sub-segmental branches bilaterally. The patient was transferred to the intensive care unit (ICU) with profound bleeding from all incisions and a massive transfusion protocol was instituted. ECMO flows varied, depending on the intravascular volume status of the patient. The patient was cooled to 33 o C for cerebral protection. Initial blood work 5 minutes on from the initiation of ECMO revealed a pH of 7.10 and lactate >15 mmol/L. Over the next 12 hours, oxygen saturations in the right arm began to fall (29% right vs. 77% left); as the left ventricular ejection improved, the heart began to eject deoxygenated blood from the impaired pulmonary system. At the same time, the patient was developing an abdominal compartment syndrome from ongoing intraperitoneal bleeding. To avoid hypoxic cerebral and myocardial disruption of arterial ECMO flows from the femoral vessels during laparotomy, the decision was made to switch from the femoral to central right axillary artery cannulation in the hope of improving brain oxygenation for the procedure. The patient's hemodynamics and coagulation status stabilized, but, over the next few days, she developed a right arm compartment syndrome, requiring fasciotomies. At this time, her myocardial function improved and the patient was converted from V-A ECMO to a single, dual-lumen Avalon cannula for veno-venous (V-V) ECMO through the right internal jugular vein. It was felt that the lungs required more time to recover, therefore, V-V ECMO was used. The patient was weaned from V-V ECMO successfully on post-operative day (POD) 4. The duration of ECMO was 3.5 days (81 hours). The patient required 4 cannulation sites to optimize flow and perfusion with changing clinical conditions. On POD 46, the patient was discharged from hospital without any physical or neurological sequelae.